Mеat products for nutrition of people with the overweight of body – pandemia pf XXI centure - Peshuk, Ludmila; Galenko, Oleg; Androsova, Anastasia; Bohun, Vladimir (My University, 2016)
A basic task in solving a problem of overweight is development of such special foods which would give an opportunity to the people with the overweight of body to bring down body weight, consuming that or other product. Such effect can be attained by adding or changing a certain component in compounding by other one with high functional properties. Основним завданням у вирішенні проблеми надмірної ваги є розробка таких спеціальних продуктів харчування, які б дали можливість людям із надмірною вагою тіла знизити масу тіла, вживаючи той чи інший продукт. Такого ефекту можна досягти, додаючи або замінюючи певний компонент у рецептурі іншим з високими функціональними властивостями.
Keywords: кафедра технології м’яса і м’ясних продуктів; функціональні продукти; guinea fowl meat; overweight; надлишкова вага; м'ясо цесарок